Bahaya ergonomi usaha jasa makan minum: Sebuah tinjauan literatur - Anashir, Muhammad Iqbal; Syahadat, Ray March; Zulfa, Nely (Jounal of Enviromental Science Sustainable, 2023)
It is well known that there are still limited literature related to the dangers of ergonomics in the food and beverage industry, especially in Indonesia. In fact, this industry is very developed in recent times. This article aims to provide information with a literature review related to ergonomic hazards in the food and beverage industry in the last five years. The method used is scientific articles searched using Google Scholar. The results obtained in the last five years, the most reported ergonomic risks are musculoskeletal. Rapid Entire Body Assessment and Ovako Work Posture Analysis System are methods that can be an alternative to identify ergonomic hazards in the food and beverage industry. Education, creation and redesign of space and equipment to prevent ergonomic hazards is a future challenge to achieve occupational safety and health and support work productivity.